CLINICAL RECOMMENDATIONS ON DIAGNOSTICS AND TREATMENT OF SEVERE SEPSIS AND SEPTIC SHOCK IN MEDICAL UNITS OF ST. PETERSBURG - V. A. Rudnov (Вестник анестезиологии и реаниматологии)
The letter contains comments on the draft clinical recommendations for diagnostics and treatment of severe sepsis and septic shock in medical units of St. Petersburg, prepared by St. Petersburg Society of Sepsis Specialists (www.spbsepsis.ru). The number of principal comments has been stated and the opinion is expressed that the use of publication of these recommendations in the present form is doubtful.